2022
DOI: 10.1002/tea.21795
|View full text |Cite
|
Sign up to set email alerts
|

Embracing equity and excellence while constructing science teacher identities in urban schools: Voices of new Teachers of Color

Abstract: We explored how new Teachers of Color grappled with equity and excellence as they were constructing science teacher identities while learning to teach in a teacher education program committed to equity, justice, and excellence, and eventually teaching in urban schools where inequities and injustices persist. The theoretical framing, compiled from various bodies of literature, weaved together what we consider as essential parts of teacher identity construction and provided a lens with which to examine how conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Moreover, the design of science professional learning along with a more student-centered, justice-oriented curriculum are effective in supporting teachers to transform their science teacher identities. Our study extends the work of Chen and Mensah [5] and Varelas, Segura, Bernal-Munera, and Mitchener [37] by examining the confluence of a justice-centered elementary STEM curriculum to transform the science teaching identities and the instructional practices of two Baltimore City elementary teachers.…”
Section: Justice-centered Science Curriculum and Pedagogymentioning
confidence: 64%
See 3 more Smart Citations
“…Moreover, the design of science professional learning along with a more student-centered, justice-oriented curriculum are effective in supporting teachers to transform their science teacher identities. Our study extends the work of Chen and Mensah [5] and Varelas, Segura, Bernal-Munera, and Mitchener [37] by examining the confluence of a justice-centered elementary STEM curriculum to transform the science teaching identities and the instructional practices of two Baltimore City elementary teachers.…”
Section: Justice-centered Science Curriculum and Pedagogymentioning
confidence: 64%
“…Chen and Mensah [5] and Varelas, Segura, Bernal-Munera, and Mitchener [37] examines the interaction between teacher identity and more inclusive, justice-focused pedagogy and found that a social justice orientation is influenced by the larger institutional context and more local school-based context of each educator. Moreover, the design of science professional learning along with a more student-centered, justice-oriented curriculum are effective in supporting teachers to transform their science teacher identities.…”
Section: Justice-centered Science Curriculum and Pedagogymentioning
confidence: 99%
See 2 more Smart Citations
“…Pennington and Prater (2016) illustrate well how taken‐for‐granted assumptions and white privilege could produce a “veil” that hinders meaning making—especially, in culturally diverse contexts. Some scholars in teacher education have drawn from critical race and feminist traditions to articulate their own identities and positionalities, using positionality as an explicit tool of analysis in identity research (Chen & Moore Mensah, 2022; Martin & Gholson, 2012; Mensah, 2012; Morales‐Doyle, 2018; Rivera, 2022; Rodriguez & Navarro‐Camacho, 2022; Tolbert et al, 2018; Varelas et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%